DIGITALISASI PENCATATAN KEUANGAN HARIAN UMKM WARUNG BUDE SRI MELALUI APLIKASI “BUKU WARUNG” - Agung Priyono; Devi Safitri; Dita Hanum; Ilena Putri Aisyah; Muhammad Nurfikri Kurniadi; Reny Andriyanty (Jurnal Pengabdian Teratai, 2025)
This training activity aims to improve the financial literacy of micro-business owners at Warung Bude Sri in using the BukuWarung app for digital financial record-keeping. The main problem faced by Toko Ibu Sri is that financial records are still kept manually and are not properly organized, making it difficult to manage the business. Through hands-on practice and personal guidance, participants were trained to create accounts, record transactions, and review digital financial reports independently. The training results showed a thirty percent increase in participants' understanding and skills in managing finances digitally. Participants were also able to produce simple digital financial reports that aid in business decision-making. This activity successfully encouraged the implementation of financial digitalization among MSMEs.